Functionalized Terpolymer-Brush-Based Biointerface with Improved Antifouling Properties for Ultra-Sensitive Direct Detection of Virus in Crude Clinical Samples - Forinová, Michala; Pilipenco, Alina; Víšová, Ivana; Lynn, N Scott; Dostálek, Jakub; Mašková, Hana; Hönig, Václav; Palus, Martin; Selinger, Martin; Kočová, Pavlína; Dyčka, Filip; Štěrba, Jan; et al. (ACS applied materials & interfaces, 2021)
New analytical techniques that overcome major drawbacks of current routinely used viral infection diagnosis methods, i.e., the long analysis time and laboriousness of real-time reverse-transcription polymerase chain reaction (qRT-PCR) and the insufficient sensitivity of "antigen tests", are urgently needed in the context of SARS-CoV-2 and other highly contagious viruses. Here, we report on an antifouling terpolymer-brush biointerface that enables the rapid and sensitive detection of SARS-CoV-2 in untreated clinical samples. The developed biointerface carries a tailored composition of zwitterionic and non-ionic moieties and allows for the significant improvement of antifouling capabilities when postmodified with biorecognition elements and exposed to complex media. When deployed on a surface of piezoelectric sensor and postmodified with human-cell-expressed antibodies specific to the nucleocapsid (N) protein of SARS-CoV-2, it made possible the quantitative analysis of untreated samples by a direct detection assay format without the need of additional amplification steps. Natively occurring N-protein-vRNA complexes, usually disrupted during the sample pre-treatment steps, were detected in the untreated clinical samples. This biosensor design improved the bioassay sensitivity to a clinically relevant limit of detection of 1.3 × 104 PFU/mL within a detection time of only 20 min. The high specificity toward N-protein-vRNA complexes was validated both by mass spectrometry and qRT-PCR. The performance characteristics were confirmed by qRT-PCR through a comparative study using a set of clinical nasopharyngeal swab samples. We further demonstrate the extraordinary fouling resistance of this biointerface through exposure to other commonly used crude biological samples (including blood plasma, oropharyngeal, stool, and nasopharyngeal swabs), measured via both the surface plasmon resonance and piezoelectric measurements, which highlights the potential to serve as a generic platform for a wide range of biosensing applications.
Keywords: Biofouling; Limit of Detection; RNA virová; limita detekce; Sensitivity and Specificity; senzitivita a specificita; Humans; fosfoproteiny; piezoelectric biosensor; biotest; functional coatings; Biosensing Techniques; polymerázová řetězová reakce s reverzní transkripcí; nosní sliznice; lidé; Reverse Transcriptase Polymerase Chain Reaction; biosenzitivní techniky; koronavirové nukleokapsidové proteiny; Nasal Mucosa; reprodukovatelnost výsledků; rapid detection; polymery; COVID-19; Nasopharynx; Polymers; bioznečištění; Biological Assay; Reproducibility of Results; zwitterionic materials; Coronavirus Nucleocapsid Proteins; COVID-19 Testing; nazofarynx; RNA, Viral; Specimen Handling; testování na COVID-19; odběr biologického vzorku; polymer brush; SARS-CoV-2; ionty; hmotnostní spektrometrie; Phosphoproteins; Ions; Mass Spectrometry